Influence of body composition, muscle strength, and physical performance on the postoperative complications and survival after radical gastrectomy for gastric cancer: A comprehensive analysis from a large-scale prospective study. Issue 5 (May 2021) - Dong, Qian-Tong; Cai, Hui-Yang; Zhang, Zhao; Zou, Hong-Bo; Dong, Wen-Xi; Wang, Wen-Bin; Song, Hao-Nan; Luo, Xin; Chen, Xiao-Lei; Huang, Dong-Dong
Summary: Background: Few studies have comprehensively analyzed the correlations among body composition parameters, muscle strength, and physical performance, as well as the influence of these factors on the postoperative complications and survival after radical gastrectomy for gastric cancer. Methods: A prospective study was conducted including patients who underwent radical gastrectomy for gastric cancer from August 2014 to June 2019. Skeletal muscle index (SMI), skeletal muscle density (SMD), visceral fat area (VFA), subcutaneous fat area (SFA) was obtained by measurement of preoperative computed tomography (CT) images. Grip strength and 6-m gait speed were measured to assess muscle strength and physical performance before surgery. Results: There was a positive correlation between SMI and SMD, as well as between SFA and VFA. SMD negatively correlated with SFA and VFA. SMI had a positive correlation with VFA, but showed minimal correlation with SFA and visceral to subcutaneous fat ratio (VSR). Grip strength and gait speed were both positively correlated with SMI and SMD, but showed minimal correlation with SFA, VFA and VSR. SMI and grip strength independently predicted postoperative complications, rather than SMD or gait speed. Whereas SMD and gait speed had independent predictive value for overall survival (OS) and/or disease-free survival (DFS), rather than SMI or grip strength. VSR independently predicted postoperative complications, rather than VFA or SFA alone. Low SFA was an independent risk factor for OS and DFS. High VFA was associated with worse survival in overweight patients (body mass index, BMI ≥25), but was associated with better survival in non-overweight patients (BMI <25). High SFA did not significantly influence survival in overweight patients, but was associated with better survival in non-overweight patients. Conclusion: There is an extensive and complex correlation among body composition parameters, grip strength, and gait speed in patients with operable gastric cancer. A comprehensive analysis of these parameters has significant predictive value for postoperative complications and survival.